2008
DOI: 10.4269/ajtmh.2008.79.755
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Rapid Test on Umbilical Cord Blood to Screen for Trypanosoma cruzi Infection in Pregnant Women in Argentina, Bolivia, Honduras, and México

Abstract: We conducted a cross-sectional study of Chagas disease in five endemic areas in Argentina, Bolivia, Honduras, and México to estimate the prevalence of Trypanosoma cruzi-specific antibodies in pregnant women, and to assess the use of a rapid test (Chagas Stat-Pak) to screen for T. cruzi infection at the time of delivery. The prevalence of antibodies to T. cruzi measured by enzyme-linked immunosorbent assay (ELISA) in maternal blood was 5.5% (a range of 0.8-28.8% among the countries) in 2,495 women enrolled. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 21 publications
7
64
1
1
Order By: Relevance
“…Immunochromatographic dipstick tests have been developed for a range of tropical diseases, including malaria (31), leishmaniasis (7), and schistosomiasis (3); until recently (4,5,8,14,17,20,25,28,30), none was available for Chagas disease.…”
mentioning
confidence: 99%
“…Immunochromatographic dipstick tests have been developed for a range of tropical diseases, including malaria (31), leishmaniasis (7), and schistosomiasis (3); until recently (4,5,8,14,17,20,25,28,30), none was available for Chagas disease.…”
mentioning
confidence: 99%
“…25 We studied 2,495 pregnant women in Argentina, Bolivia, Honduras, and Mexico and found a sensitivity of 94.6% and a specificity of 99.0% for the Chagas Stat-Pak in cord blood compared with the Wiener ELISA in maternal blood. 18 We also compared these commercial tests (Stat-Pak and ELISA Wiener) with non-commercial tests using a local Mexican strain of T. cruzi and found similar results for both tests in umbilical cord blood samples. 19 Blood samples were centrifuged, and serum samples (5 μL) were used for Stat-Pak rapid tests according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…16 We estimated in a previous article that about 37,000 pregnant women and 1,800 newborns are likely to be infected with T. cruzi in Mexico. 17 In a recent study, we identified 5 seropositive mothers of 500 women who gave birth at an urban hospital in Mérida, Yucatá n. 18 Newborn children of seropositive mothers were tested for presence of T. cruzi antibodies 10 months after birth to determine potential congenital infection. None of the children were seropositive.…”
Section: Introductionmentioning
confidence: 99%
“…96%. (Ponce et al, 2005;Brutus et al, 2008;Roddy et al, 2008;Sosa-Estani et al, 2008) The fundamental problems of T. cruzi infection serological diagnostic methods are the lack of reproducibility that sometimes occur, deficient immunological reaction specificity, what produces false-positive results, and the occasional insufficient sensitivity translated into false-negative outcomes. Chagasic infection serology tests may produce cross-reactions with antibodies produced during the course of other illnesses.…”
Section: Serological Diagnosis Of Chronic Entitiesmentioning
confidence: 99%